Teacher knowledge in English language teaching : an analysis of its socio-historical construction in the western central region of Costa Rica = Saber docente en profesores de inglés : un análisis sobre su construcción socio-histórica en la Región Central Occidental de Costa Rica - Araya Araya, Karla 1980-
This article results from a research project developed in Costa Rica, specifically, in the central western region. Its main objective is of findings that shed light on the socio-historical principles and construction of teacher knowledge of English language teaching. Teacher knowledge is approached as a discursive and everyday life construction whose historical antecedents influence its constitution and perception. Therefore, an analysis of the historical situations that justified the English language teaching in Costa Rica is provided. Also, it is analyzed the way(s) national institutions like the "Ministerio de Educación Pública" as well as the English language teaching major from "Sede de Occidente, Universidad de Costa Rica" have historically assumed and set the principles of teacher knowledge. This study concludes that there have been four main domains regulating the English language teacher knowledge. They are the technical, the institutional, the content and the economic domains.